Cardiovascular Diseases Among Indian Older Adults: A Comprehensive Review - Bisma Jan; Mohammad Imran Dar; Bharti Choudhary; Parakh Basist; Rahmuddin Khan; Abdulsalam Alhalmi (Hindawi-Wiley, 2024)
Cardiovascular diseases (CVDs) constitute an important cause of morbidity and mortality globally, and India is no exception to this trend. With the ongoing aging of the population in India, there is a notable surge in the prevalence and impact of CVDs among older adults. This review is aimed at providing a comprehensive overview of the current knowledge concerning the prevalence, risk factors, and management of CVDs in the context of Indian older adults. The incidence of CVDs in India is not only alarming but also exhibits an upward trajectory with advancing age. Primary risk factors contributing to the elevated incidence among older adults include hypertension (HT), diabetes, dyslipidemia, obesity, smoking, a sedentary lifestyle, and poor dietary habits. Additionally, stress and genetic predisposition emerge as noteworthy contributors to CVDs in this population. Effectively identifying and managing these risk factors among older adults in India is imperative to alleviate the burden of these diseases and enhance overall quality of life. Strategies aimed at mitigating the impact of CVDs in the country necessitate a comprehensive approach, integrating lifestyle interventions, public health initiatives, and a robust healthcare system. In summary, CVDs represent a significant health concern in both rural and urban areas of India. However, variations exist in the prevalence, risk factors, and accessibility to healthcare between these regions. Therefore, addressing the prevalence of CVDs in India necessitates a complex, multidimensional strategy that takes into account the unique opportunities and challenges that come with living in both rural and urban areas.